Adapter et commenter le Livre des Rois (Shâhnâmeh) en Allemagne au XIXe siècle - Christine Maillard (Recherches Germaniques)
The reception of the Shâhnâmeh (Book of Kings) holds a place apart in the array of Eastern sources made available in Europe. Ferdowsi’s work was the subject of presentations in the Orientalist journals that appeared after 1800, including Treasure Trove of the Orient (Fundgruben des Orients) launched in 1808 by Josef von Hammer-Purgstall (1774-1856), who, like William Jones (1746-1794), was a pioneer of European orientalism. Jules Mohl (1800-1876), a Francophone and Francophile German, marked a crucial turn in the reception of the Book of Kings with his full French translation published between 1838 and 1778. In Germany the interest for Ferdowsi’s work was considerable during the whole 19th century, with some important translations like those of A. F. von Schack (1851) and Friedrich Rückert (1890). But the first and perhaps most important of this German translations was made by Joseph Görres (1776-1848), who published Das Heldenbuch von Iran. Aus dem Schah Nameh des Firdussi in 1820, with an introductive commentary of more than one hundred pages. Our paper will analyse for the first time this important paratext, as a testimony of the link between translation, interpretation of history and seeking for national identity, in the context of developing contemporary myth theories.